Residual effects of superficial liming on tropical soil under no-tillage system - Martins da Costa, Claudio Hideo (2016)
The objective of this work was to evaluate the long-term effects of the surface application of lime on soil fertility and on the mineral nutrition and grain yield of soybean, and of black oat and sorghum in crop succession. The experiment was carried out on a clayey Oxisol, in a randomized complete block design, with four replicates. Treatments consisted of lime the rates of 0, 1,000, 2,000, and 4,000 kg ha(-1), applied in October 2002 and November 2004. Soil samples were collected at five soil layers, down to 0.60-m depth. Surface liming was effective in reducing soil acidity and increasing Ca2+ and Mg2+ contents in the subsurface. Moreover, it increased available phosphorus contents and soil organic matter in the long term (48 to 60 months after the last lime application). Surface liming improved plant nutrition, mainly for N, Ca, and Mg, and increased dry matter production and grain yield of the crops, even in years with regular distribution of rainfall. The greatest productivities of soybean, black oat, and sorghum were obtained with the respective estimated lime doses of 4,000, 2,333, and 3,281 kg ha(-1), for shoot dry matter, and of 2,550, 3,555, and over 4,000 kg ha(-1), for grain yield.